Profile of maladaptive and normative eating behaviors in correlation with rumination: a cross-sectional study among Lebanese adults - Emmanuelle Awad; Diana Malaeb; Mirna Fawaz; Lara Youssef; Anna Brytek-Matera; Souheil Hallit; Sahar Obeid (Psicologia: Reflexão e Crítica)
Abstract Background Dieting is a common practice around the world. People who wish to lose weight, improve their eating habits, or reach a desired level of health often diet. Rumination, a pattern of repetitive negative thoughts and emotions, is typically found when individuals diet. The current study aimed to identify physical and psychological differences between maladaptive and normative eating behaviors in a sample from Lebanon. Methods A cross-sectional design was adopted for the current study. It occurred between June and July 2022. Four hundred participants aged 18 and above participated. The research team used a snowball sampling method to recruit volunteers from all governorates of Lebanon. Results Beta values were used to compare independent variables in order to infer those that have the strongest effect on the dependent ones. Higher Body Mass Index, and belonging to cluster 3 (restriction of food intake and rumination) and cluster 1 (maladaptive eating behavior and rumination) compared to cluster 2 (normative eating behavior and thought) were significantly related to more dieting. Higher physical activity index and belonging to cluster 3 (restriction of food intake and rumination) and cluster 1 (maladaptive eating behavior and rumination) compared to cluster 2 (normative eating behavior and thought) were significantly related to higher levels of orthorexia nervosa tendencies. Conclusions The current research demonstrated a relationship between Body Mass Index, physical activity, rumination, and maladaptive eating patterns including restriction of food intake, dieting, and orthorexia nervosa. These results can help with identifying physical and psychological factors associated with maladaptive eating patterns, as well as guide interventions within the Lebanese population.